Prediction of Onset Fluidization Using Critical Rayleigh Number. - Tan, Yee Wan (2004)
The incipient instability in gas fluidized bed has not been fully understood despite extensive studies were conducted. A new transient theory was proposed by adopting the principles advanced by Tan and Thorpe (1992 and 1996) and Tan et al. (2003), and this was verified by computational fluid dynamic (CFD) simulations. The theory of instability in porous media has two functions. One involved the molecular diffusion of a microscopic mass flux in the gas phase with potential adverse density gradient, buoyancy convection in gas will occur, but the solid particles will stationary. If t he solid p articles w ere subjected t o very high m ass fluxes which i s characterized by its high gas velocity such as those exceeding the minimum velocity of fluidization, then the buoyancy force o f t he p articles will b e overcome and the solids will be moved and fluidized almost instantaneously 2D time dependent simulations were conducted using a CFD package - FLUENT for gas diffusion in porous media to observe buoyancy convection and also the incipient instability in fluidized bed, using various gas pairs, mass fluxes and particles sizes. The simulation conducted was validated and verified by comparison with the experimental data from literature. As a prelude to these studies, transient convection induced by gas diffusion in another gas was conducted, so as to understand fully the instability induced by mass diffusion. The simulated critical Rayleigh number were found to be 531 and 707 for top-down and bottom-up gas-gas diffusion respectively, which were very close to the theoretical value of 669 and 817. For transient buoyancy instability induced by gas diffusion in porous media, the average simulated critical Rayleigh number was found to be 26.7, which agreed very well with the theoretical value of 27.1. The simulated onset time of buoyancy convection were also found to be in good agreement with the predicted value. Incipient instability in fluidized bed is caused by fluid velocity higher than the minimum fluidization velocity, U,f. The simulations of incipient instability showed that the bed behavior was dependent on the fluid velocity and the particle size and porosity. The incipient instability was preceded by the gas or pressure saturation of the interstices, induced a high momentum force due to the high mass flux which mobilized and lifted the particles once the critical Rayleigh number was exceeded. The simulated critical Rayleigh number was found to be 30.4, which agreed with the theoretical value of 27.1 for buoyancy instability in porous media. The simulated critical times o f t he incipient instability in fluidized bed were in good agreement with the predicted values and reported experiments in literature. The bed pressure drop, expansion ratio and void fraction after the fluidization were successfully simulated and were found to be in good agreement with experiments and theoretical values.